Empowering Young Minds: Exploring Social Development And Environmental Awareness Through Recycled Waste Crafts In Pandanlandung Village Children’s Forum - Nashihah, Durratun; Shearen, Jessica; Putri, Kanila; Suryawati, Julia; Maulana, Ilham Nur Hanifan; Dinata, Chandra (Jurnal Masyarakat Madani Indonesia, 2025)
Using recycled garbage craft activities, this study investigates how a Children's Forum in Pandanlandung Village affects the social development and environmental consciousness of children aged 4 to 17. Using direct observation, participant and facilitator interviews, and recording of produced works, data were gathered using a descriptive and qualitative approach. Children's social skills—including cooperation, communication, and empathy—which result from their involvement in practical recycling projects show significant increases. Apart from teaching youngsters on proper trash management and the need of environmental preservation, the activities promoted social connection, particularly after the COVID-19 outbreak. Children who turned trash into art developed agency, self-esteem, and responsibility toward their environment and society. This project shows how creatively minded educational programs could improve children's complete development and foster a sustainable culture. These results emphasize the need of similar programs in different settings and their ability to empower teenagers as active agents of change in building better, environmentally conscious communities.